2014
DOI: 10.1093/toxsci/kfu191
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Events Determine Tissue-Specific Toxicity of Inhalational Exposure to the Genotoxic Chemical 1,3-Butadiene in Male C57BL/6J Mice

Abstract: 1,3-Butadiene (BD), a widely used industrial chemical and a ubiquitous environmental pollutant, is a known human carcinogen. Although genotoxicity is an established mechanism of the tumorigenicity of BD, epigenetic effects have also been observed in livers of mice exposed to the chemical. To better characterize the diverse molecular mechanisms of BD tumorigenicity, we evaluated genotoxic and epigenotoxic effects of BD exposure in mouse tissues that are target (lung and liver) and non-target (kidney) for BD-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 44 publications
2
31
0
Order By: Relevance
“…• Significant variability in tissues and experimental paradigms can exist, so confidence in data interpretation from non-target tissue, in vitro cell lines or, to a lesser extent, from primary cell cultures will be increased by coherence with other evidence streams [38];…”
Section: Methods and Considerations In The Application Of Epigeneticsmentioning
confidence: 99%
“…• Significant variability in tissues and experimental paradigms can exist, so confidence in data interpretation from non-target tissue, in vitro cell lines or, to a lesser extent, from primary cell cultures will be increased by coherence with other evidence streams [38];…”
Section: Methods and Considerations In The Application Of Epigeneticsmentioning
confidence: 99%
“…The extent of global DNA hypomethylation was strain-specific and also varied across target and non-target tissues of 1,3-butadiene-induced carcinogenesis [161, 162]. For example, a loss of methylation within repetitive DNA elements was observed in the lung and liver (target tissues of carcinogenesis), but not in the kidney (non-target tissue of carcinogenesis) in C57BL/6J mice.…”
Section: Epigenetic Effects Associated With Carcinogenic Chemicalsmentioning
confidence: 99%
“…Loss of these histone modifications is known to impair the maintenance of proper chromatin structure, diminish cellular maintenance and regulation of the cell cycle, disrupt the balance between cell proliferation and differentiation, and severely reduce cell viability [163, 164]. These histone modifications in the liver have also been shown to vary across several inbred mouse strains, as well as in target and non-target tissues of carcinogenesis [161, 162]. Interestingly, an increase in the repressive histone marks H3K9me3, H3K27me3, and H4K20me3 was observed in the kidney, a non-target tissue of carcinogenesis, in C57BL/6J mice that were subjected to short-term exposure to 1,3-butadiene.…”
Section: Epigenetic Effects Associated With Carcinogenic Chemicalsmentioning
confidence: 99%
“…Importantly, this study demonstrated the dose-dependent response, where exposure to higher concentrations of 1.3-butadiene was associated with the more pronounced loss of methylation within the TEs. Subsequent studies have shown that these effects were strain- [161] and tissue- [162] specific. Furthermore, 1,3-butadiene-induced hypomethylation of TEs was associated with their subsequent reactivation [160].…”
Section: Transposable Elements and Environmental Contaminantsmentioning
confidence: 99%